Poly(lactic-co-glycolic acid)(PLGA)/TiO2 nanotube bioactive composite as a novel scaffold for bone tissue engineering: In vitro and in vivo studies. (May 2018) - Eslami, Hossein; Azimi Lisar, Hamidreza; Jafarzadeh Kashi, Tahereh Sadat; Tahriri, Mohammadreza; Ansari, Mojtaba; Rafiei, Tohid; Bastami, Farshid; Shahin-Shamsabadi, Alireza; Mashhadi Abbas, Fatemeh; Tayebi, Lobat
Abstract: The aim of this study was to synthesize and characterize novel three-dimensional porous scaffolds made of poly (lactic-co-glycolic acid)/TiO2 nanotube (TNT) composite microspheres for bone tissue engineering applications. The incorporation of TNT greatly increases mechanical properties of PLGA/TNT microsphere-sintered scaffold. The experimental results exhibit that the PLGA/0.5 wt% TNT scaffold sintered at 100 °C for 3 h showed the best mechanical properties and a proper pore structure for tissue engineering. Biodegradation test ascertained that the weight of both PLGA and PLGA/PLGA/0.5 wt% TiO2 nanotube composites slightly reduced during the first 4 weeks following immersion in SBF solution. Moreover, the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay and alkaline phosphatase activity (ALP activity) results represent increased cell viability for PLGA/0.5%TNT composite scaffold in comparison to the control group. In vivo studies show the amount of bone formation for PLGA/TNT was approximately twice of pure PLGA. Vivid histologic images of the newly generated bone on the implants further supported our test results. Eventually, a mathematical model showed that both PLGA and PLGA/TNT scaffolds' mechanical properties follow an exponential trend with time as their degradation occurs. By a three-dimensional finite element model, a more monotonous distribution of stress was present in the scaffold due to the presence of TNT with a reduction in maximum stress on bone.